COVID 19: Myths and Facts - Gurmeet Singh Sarla (Research & Review: Management of Emergency and Trauma Nursing (e-ISSN: 2582-0494), 2020)
The clinical spectrum of COVID-19 varies from being asymptomatic to clinical conditions characterized by respiratory failure. Management of the disease is mostly supportive in the form of oxygen supplementation, noninvasive ventilation and in severe cases, mechanical ventilation. There is no specific antiviral treatment available nor is there any vaccine available. The most important step to curb this disease is prevention of the spread by social distancing and strict hand hygiene. This review article describes various myths and facts about COVID-19 and various preventive measures which should be followed to limit the spread of this disease.